REALISATION OF THE EUROPE 2020 STRATEGY AND THE STRUCTURAL FUNDS ALLOCATION BY THEMATIC FIELD OF INTERVENTION IN EUROPEAN REGIONS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
The European Union Cohesion Policy provides financial support through EU funds and gives a unique opportunity for member states and their regions to successfully combat the obstacles of a challenging environment as well as to promote its (smart, sustainable, inclusive) growth and development. In the last programming period of 2014-2020 the Policy has been aligned with the Europe’s strategy for growth and employment, Europe 2020. The regional allocation of funding has changed, where a more focused thematic concentration of financial resources is needed. There are (constant) discussions about measuring the progress towards meeting the objectives of the Europe 2020 which is connected with the implementation of the Cohesion Policy.The aim of this paper is twofold: firstly, to give a brief overview of the connection between the reformed Cohesion Policy and strategy Europe 2020 in the last programming period of 2014-2020 and secondly, to empirically analyse whether the allocation of EU funds regarding different thematic fields of intervention can be connected with the success in the realization of the strategy Europe 2020. The findings suggest that the heterogeneity in the realisation of Europe 2020 on a regional level is connected with the structure of EU funds allocation. The conclusions of this paper can be useful in monitoring the achievement of Europe 2020, in evaluating the results and possible recasting of the Cohesion Policy.